Prognostic implication of erector spinae muscles in non‐small‐cell lung cancer patients treated with immuno‐oncology combinatorial chemotherapy. Issue 21 (2nd October 2021) - Araki, Taisuke; Kitaguchi, Yoshiaki; Suzuki, Yusuke; Komatsu, Masamichi; Sonehara, Kei; Wada, Yosuke; Tateishi, Kazunari; Hanaoka, Masayuki
Abstract: Background: The quantity of skeletal muscles has recently been reported to have prognostic value in patients with non‐small‐cell lung cancer (NSCLC) treated with second‐line immunotherapy. However, the prognostic role of skeletal muscle assessment in NSCLC patients undergoing first‐line immuno‐oncology (IO) combinatorial treatment (IO‐chemotherapy) has not been elucidated. Methods: We retrospectively reviewed 36 patients with NSCLC undergoing first‐line IO‐chemotherapy between April 2018 and June 2021 in our hospital. The cross‐sectional area of the erector spinae muscle (ESMCSA ) was evaluated by manual tracing on computed tomography scans at the level of the 12th thoracic vertebra before initiating IO‐chemotherapy. To minimize deviation due to physique, the ESMCSA was adjusted by body surface area (BSA) (ESMCSA to BSA ratio: ESMCSA /BSA). A survival time analysis was performed using the Kaplan–Meier method and log‐rank test. A multivariate analysis with Cox proportional hazards model was conducted to investigate the prognostic value of the ESMCSA /BSA and inflammatory and nutritional indices. Results: The median progression‐free survival (PFS) and overall survival (OS) were 6.5 and 16.6 months, respectively. Intergroup comparison by the log‐rank test revealed that there was no significant difference in the median PFS, but the median OS was significantly long in the high ESMCSA /BSA (>19 cm 2/ m 2 ) (high ESMCSA /BSA group, p  = 0.0373). The multivariate analysis showed that ESMCSA /BSA was an independent prognostic factor for OS (hazard ratio 0.79, p  = 0.044). Conclusions: The results of this study indicate that the pretreatment ESMCSA /BSA may be a potential prognostic factor in NSCLC patients receiving first‐line IO‐chemotherapy. Abstract : In non‐small‐cell lung cancer patients undergoing first‐line immuno‐oncology combinatorial treatment, pretreatment erector spinae muscle/body surface area (ESMCSA /BSA) was associated with survival outcome. The lower ESMCSA /BSA group had significantly shorter overall survival. This finding was validated by the multivariate analysis performed in this study.